The Role of Language in Constructing Political Image on Social Media: A Critical Discourse Analysis - Akromi, Elok Nur Affah Al; Santika, Rani (Riviera Publishing, 2024)
This study explores the role of language in shaping the political identities of public figures through social media platforms. Employing Critical Discourse Analysis (CDA), the research investigates how political figures use linguistic strategies such as framing, metaphors, and modality to construct and reinforce their political personas. The analysis focuses on political discourse across three major platforms—Twitter, Facebook, and Instagram—examining how each platform's unique features influence the linguistic strategies employed. The study reveals that framing is the dominant strategy used by political figures to position themselves ideologically, while metaphors are frequently employed to evoke strong emotional responses and engage followers. Modality, particularly the use of modal verbs, plays a critical role in asserting authority and managing public expectations. The research also highlights the differences in communication styles across platforms and ideologies, showing how conservative and progressive political figures tailor their language to appeal to specific audiences. This study contributes to the understanding of how political figures use language as a tool for identity construction and public engagement in the digital era.